Sustainable Tourism and Housing Development for Panggang Island, Seribu Islands Jakarta: Learning from Maldives' Sustainable Tourism Development - Gunawan Tanuwidjaja; Mustakim (ATRIUM: Jurnal Arsitektur, 2022)
In 2016, Indonesia's tourism sector contributed 4 per cent of the Indonesian Gross Domestic Product (GDP). By 2019, the Indonesian Government wants to increase the tourism contribution to 8 per cent of GDP, requiring 20 million tourist visits. Ten "New Bali" destinations have been developed by President Jokowi, including the Seribu Islands Regency. Seribu Islands, located in Jakarta Capital Region, has various potentials and problems, such as economic disparity, rising seawater levels, declining fisheries production, limited water resources, and environmental pollution. Some Neighborhood Units (Rukun Warga) in the Seribu Islands are slums, including Panggang Island. Therefore, an Integrated Kampung Improvement (Muhammad Husni Thamrin Plus Program) was proposed. This study is prepared to identify potential concepts for spatial rezoning of Panggang Island, integrating sustainable tourism and housing neighbourhood redevelopment. The research problems are how can the community create a healthier and safer home, how can the sustainable 'tourist lodge' model in Panggang Island, and what concept of spatial rezoning of Panggang Island can be proposed. To understand the integration of tourism and residential development, we conducted Case Study Research (CSR) to learn from the Maldives Islands and implemented a qualitative approach of Strength, Weaknesses, Opportunities, and Threats (SWOT) analysis for Panggang Island. Based on the SWOT, we propose a rezoning concept for sustainable Panggang Island, integrating potential tourism zones, new fisher's housing zones, polder infrastructures, utilities, and green zones. Further, in the COVID-19 Era, an additional review on personal tourism was conducted to propose sustainable tourism activities on the Panggang Island while reducing the spread of COVID-19.